Impact of autologous haematopoietic stem cell transplantation on disability and brain atrophy in secondary progressive multiple sclerosis. (January 2021) - Mariottini, Alice; Filippini, Stefano; Innocenti, Chiara; Forci, Benedetta; Mechi, Claudia; Barilaro, Alessandro; Fani, Arianna; Carlucci, Giovanna; Saccardi, Riccardo; Massacesi, Luca; Repice, Anna Maria
Background: Autologous haematopoietic stem cell transplantation (aHSCT) is a valuable option in aggressive relapsing–remitting multiple sclerosis (MS), but its efficacy in secondary progressive (SP)-MS is still controversial. Objective: Assessing efficacy of aHSCT in SP-MS by clinical-radiological outcomes. Methods: Open-label monocentric retrospective study enrolling consecutive SP-MS patients treated with BEAM-aHSCT in the period 1999–2016. Results: In total, 26 SP-MS patients with moderate–severe disability were included. Progression-free survival (PFS) at years 5 and 10 after aHSCT were, respectively, 42% and 30%. Out of 16 patients who worsened, only 6 patients (23% overall) maintained continuous disability accrual (CDA), whereas 10 patients stabilized following one single-step Expanded Disability Status Scale (EDSS) worsening. CDA-free survival was 74% at 5–10 years. No relapses or magnetic resonance imaging (MRI) activity were reported, thus no evidence of disease activity (NEDA)-3 corresponded to PFS. Annualized rate of brain atrophy (AR-BVL) normalized after 1 year in 55% of the cases analysed (12/22). Conclusion: BEAM-aHSCT halted CDA and normalized AR-BVL in most of the treated patients, inducing long-term remission of inflammatory activity at a median follow-up of 99 months (range 27–222). These data suggest that CDA might still be mainly driven by inflammation in a subgroup of SP-MS and could therefore be reversed by treatments. CDA should be analysed independently from any isolated disability worsening.